Evaluation of leishmanicidal activity and acute toxicity of hydroalcoholic extract from stems of Croton alnifolius - Inostroza, Luis A. (2011)
This study evaluated the leishmanicidal activity and acute oral toxicity of hydroalcoholic extract from stems of Croton alnifolius. For the first, were infected with promastigotes of Leishmania peruviana, in the right hind leg, Mesocricetus auratus (hamster); after three weeks the animals were treated with the hydroalcoholic extract of Croton alnifolius. The effect of the extract was compared with sodium stibogluconate at 60 mg SbV / kg per day for 20 days. The toxic potential of hydroalcoholic extract was evaluated using the acute oral toxicity test on mice, determining the media lethal dose (LD50) with three dose levels of extract (2000, 200 and 50 mg /kg), assessing body weight and histopathological study, also was evaluated their cytotoxicity against Artemia salina. It was found that the extract has leishmanicidal activity comparable to sodium stibogluconate. The LD50 value was estimated to 1396,11 mg/kg, the Croton alnifolius extract was classified as slightly toxic, because caused slight alterations such vascular congestion in the histopathological examination. In general no evidence of significant damage or changes in their bodies, and the media lethal concentration of Artemia salina was 40,9 g/mL considered slightly toxic. Were identified the main groups of secondary metabolites present in the extract through a phytochemical screening. The results obtained allow to validate the safety of the traditional use of hydroalcoholic extract of the dried stems of Croton alnifolius to treat health problems related to leishmaniasis.